Water-Sealed Blasting Control Measures of the Metro Station Undercrossing Existing Structures in Ultra-Close Distances: A Case Study - Shi, Chenghua; Zhao, Yiwei; Zhao, Chenyang; Lou, Yili; Sun, Xiaohe; Zheng, Xiaoyue (Frontiers in Earth Science, 2022)
Based on the project of People's Hall Station of Qingdao Metro Line 4 in China, the method of water-sealed blasting construction for vibration damping is proposed, as the blasting vibration of adjacent structures (Qingdao Metro Line 3) does not meet the control requirements during the blasting construction of the existing site blasting scheme. The effects of blasting on adjacent structures with different water-sealed charge structures and different axial decoupled charge factors are first studied by using the three-dimensional dynamic numerical simulation method. On this basis, a multi-case parametric analysis is carried out on the maximum single detonation charge, initiation interval, vibration-damping hole settings, and other factors that affect the blasting seismic effect. The results demonstrate that water-sealed construction blasting can significantly reduce the vibration response of adjacent structures. The lower-water-decking charge structure, the two ends-water-decking charge structure, and the top-water-decking charge structure can reduce the vibration velocity response of adjacent structures by 2.8%, 24.5%, and 27.8%, respectively. As the axial decoupling coefficient increases, the peak resultant vibration velocity increases first and then decreases. The peak resultant vibration velocity reaches the minimum value of 1.27 cm/s, which is lowered by 29.5% when the decoupling coefficient is 2.6. The after-detonation vibration response can be reduced by decreasing the amount of a single detonation charge and setting damping holes. When the detonation charge is reduced to 2.7 kg or 100 mm damping holes are set up, the vibration velocities at Line 3 People's Hall Station are 1.10 cm/s and 1.11 cm/s, respectively. Both velocities are less than the 1.2 cm/s resultant vibration velocity control tolerance requirements. The results of this study can play an important guiding role in construction blasting in on-site metro stations and can serve as a reference for future similar projects.